2014
DOI: 10.3390/s140611260
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Ultrasonic Sensing for High Resolution Measurement of Binary Gas Mixture Fractions

Abstract: We describe an ultrasonic instrument for continuous real-time analysis of the fractional mixture of a binary gas system. The instrument is particularly well suited to measurement of leaks of a high molecular weight gas into a system that is nominally composed of a single gas. Sensitivity < 5 × 10−5 is demonstrated to leaks of octaflouropropane (C3F8) coolant into nitrogen during a long duration (18 month) continuous study. The sensitivity of the described measurement system is shown to depend on the difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…However increasing ambient pressure will also compress the transducer diaphragms, which will tend to cancel out the effect of increased pressure on the calculated value of XeUFM (%). 7 Despite the above concerns, post hoc analysis showed that within normal ranges encountered in clinical practice, changes in ambient temperature and pressure had no clinically significant effect on accuracy of XeUFM (%) measurement.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However increasing ambient pressure will also compress the transducer diaphragms, which will tend to cancel out the effect of increased pressure on the calculated value of XeUFM (%). 7 Despite the above concerns, post hoc analysis showed that within normal ranges encountered in clinical practice, changes in ambient temperature and pressure had no clinically significant effect on accuracy of XeUFM (%) measurement.…”
Section: Discussionmentioning
confidence: 92%
“…Speed of sound (c) in a binary gas mixture is related to concentration, temperature, pressure, and molar masses of the component gases based on a complex non-linear relationship 2,6,7 (Figure 2) given by the equation:…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the ultrasonic sensor has been successfully used to measure the concentration of mixtures. For binary mixtures, the ultrasonic features (e.g., ultrasonic attenuation and velocity) are directly correlated with concentrations [ 6 , 7 ]. However, it is very difficult or even impossible to derive a physical model to characterize the relationship between ultrasonic features and component concentrations in multicomponent mixtures [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…7. Ultrasonic in binary gas: In [10] an ultrasonic instrument is used to measurement of leaks of a high molecular weight gas (octafluoropropane coolant, C3F8) into a system that is nominally composed of a single gas (nitrogen) during a long duration (18 month). The sensitivity of the instrument is due to the difference in molecular masses of the two gases in the mixture.…”
Section: Sewer Pipelinesmentioning
confidence: 99%